Ambidextrous Leadership Behaviors and Their Role in Organizational Immunity: An Analytical Study of the Opinions of a Sample of Doctors in a Number of Private Hospitals in the City of Erbil - Abdulrahman Zrar Abdurahman Sherwani (QALAAI ZANIST JOURNAL, 2021)
The research aims to identify the role of skillful leadership behaviors (represented by openness and closing behaviors) in achieving organizational immunity in its dimensions (organizational learning, organizational memory, organizational DNA). To achieve the objectives of the research, a questionnaire was designed to measure the reality of skilful leadership behaviors in a number of private hospitals in the city of Erbil and its impact on enhancing organizational immunity through the use of statistical methods for social sciences (SPSS)in order to test the research hypotheses, and the research concluded that Ambidextrous leadership behaviors came at an average level, with a strong impact of these behaviors in achieving organizational immunity